Campaign Strategy through the Online Newspaper 'Radar Bekasi' in Building Popularity (A Case Study of a Member of the Regional People's Representative Council from the Gerindra Party, Electoral District IX, West Java Province in the 2024 General Election) - Sahil, Mohamad; Dwinarko, Dwinarko; Widodo, Aan (Journal of Law, Politic and Humanities, 2025)
This study aims to analyze political campaign strategies through online newspaper media in shaping the popularity of the Regional House of Representatives (DPRD) members from the Gerindra Party in Electoral District 9 of West Java (Bekasi Regency) during the 2024 General Election. The main focus of this research is the use of local online media, particularly Radar Bekasi, in supporting the visibility and electability of legislative candidates. Online media is chosen for its ability to reach the public widely, quickly, and interactively, especially among young voters, the middle class, and urban communities. A qualitative descriptive approach with a case study method was used, involving in-depth interviews, observations, and documentation of elected candidates and campaign content published in the media. The findings show that consistent use of Radar Bekasi (1–2 times per month) significantly increased candidates' popularity through news coverage, advertorials, opinion articles, and reports on socio-political activities. Seven key factors influencing the effectiveness of this strategy include media reach, credibility, limitations of face-to-face campaigns, interactivity, public perception, digital media consumption trends, and editorial professionalism. The study also reveals a mutualistic relationship between candidates and local media in the campaign context. It is concluded that online newspaper media serves not only as an information platform but also as a strategic actor in shaping political image and legitimacy at the local level. These findings highlight the importance of digital media in modern campaign strategies that are adaptive and grounded in the power of political communication.